The Students' Affect toward Classroom activities on English for daily Conversation - Silfia Rahmi (Universitas Bengkulu, 2022)
Classroom activities becomes one of necessary and beneficial efforts for enhancing students’ speaking ability. However, that endeavor will be advantageous and will not waste the time if the students like them. Therefore, this research aims at investigating students’ affect toward classroom activities on English for daily conversation subject together with their reason to have such kind of that affect. This belongs to mixed method research. The instruments used to collect the data were questionnaire along with interview guide. There were 78 (Seventy Eight) students participated to obtain the quantitative data and there were 12 (twelve) students to gain the qualitative data. The data obtained from the questionnaire were analyzed based on formula suggested by Heaton and Djemari et. All. Meanwhile, the data got from interview guide were analyzed based on the theory recommended by Miles and Huberman. The finding of this research revealed that there were 80.76 % (Eighty point seventy six) students had strongly positive affect toward classroom activities applied by the lecturer on English for daily conversation subject. The reasons were the students convince that they can encourage them to speak and can increase their speaking ability and may provide the students’ opportunities to speak. Furthermore, classroom activities can express their idea creatively and can stimulate them to think quickly, critical and creative. Besides, through classroom activities, they have the bravery to speak English. It indicated that most of students like to have classroom activities. In nutshell, there are students’ positive response toward classroom activities. Then, they also have the rationale reason why they have such kind of that affect. It indicated that there were no psychological problem faced by the students when the lecturers applied classroom activities on English for daily conversation subject. It can be interpreted that the providing classroom activities which usually employed by the lecturers can be continued to be applied as an effort to increase students’ speaking ability.